Social Assessment Prioritizes Urban Water and Wastewater Problems in Russia - Kudat, Ayse (World Bank, Washington, DC, 2012)
Russia's transition to a market economy has had profound effects on its municipal water and wastewater sector. The country's overall economic downturn and severe fiscal constraints have deprived the municpal water and wastewater companies and local governments of the large subsidies they used to receive. The scarcity of resources has prevented new investment, and many wastewater companies need help to keep their systems functioning. The proposed Bank-financed project on Russia Municipal Water and Wastewater seeks to improve the water services people receive. People are the most important factor in all water supply and sanitation activities. This Note summarizes the objectives of the social assessment (SA) for the project and the SA findings. It also presents the recommendations the SA made.